1989
DOI: 10.1179/cmq.1989.28.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Model Studies of Mixing Phenomena in Stirred Melts

Abstract: Mixings were performed in a water model system of a gas-stirred ladle with both an optical decolorization method and conductivity measurements at different positions within the vessel. The experimental results show that the rate by which the concentration is homogenized depends on the location of the measuring probe as well as on the used stirring conditions, e.g. gas flow rate and position of the gas injection nozzle. Furthermore, a new theoretical mixing model that combines the concepts of the circulating co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Recently, Mazumdar et al [15] standardized the diverse experimental conditions applied by various investigators [13,14,16,17] in studying mixing phenomena in ladles to a unique set of reference conditions, through the application of appropriate criteria. They have concluded that Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Mazumdar et al [15] standardized the diverse experimental conditions applied by various investigators [13,14,16,17] in studying mixing phenomena in ladles to a unique set of reference conditions, through the application of appropriate criteria. They have concluded that Eq.…”
Section: Resultsmentioning
confidence: 99%
“…(2) The mixing performance at different monitoring points was widely studied in 1980s by Oeters and co-workers [76][77][78][79][80][81]. In 1988, Krishna-Murthy et al [82] concluded that the mixing time did not depend on the variations in the amount of tracer used.…”
Section: Discussionmentioning
confidence: 99%
“…However, various works have been reported in literature with contrasting conclusions, such as the investigations carried out by Krishna Murthy and his colleagues [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] in which the authors conclude that the measurements obtained of the mixing time do not depend on the location neither on the tracer amount released with which the conductivity technique is performed. On the other hand, various authors conclude that not only the location of the sensors 22) affects the mixing time measurements but also the location of the tracer addition [23][24][25] is a variable that considerably affects the time required to reach a homogeneity degree of 95%. The discrepancies between authors have given rise to discussions and communications 26) between authors with reference to the relevance of the influence that a location of the addition of the tracer has on the experimental measurements of mixing time.…”
Section: Introductionmentioning
confidence: 99%